A study of pituitary-adrenal hormonal responses in patients treated for chronic stress - Moch, S, L. (My University, 2005)
Objectives: To document baseline pituitary-adrenal hormonal and related metabolic variables in 16 female patients with burnout. Then, following stress management intervention, to compare the changes with an equal number of untreated control subjects.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Sciences in Medicine Johannesburg 2005
Keywords: Pituitary-Adrenal System; Growth Hormone